Remember When: A Nostalgic Trip Through the Consumer Era - Opie, Robert (London Mitchell Beazley, 2001)
Remember When presents a fascinating picture of everyday life in the 20th century - from the late Victorian era to the present day - exploring all aspects of society as reflected in the legacy of packaging, advertising, magazines and newspapers, toys and games, and royal and commemorative memorabilia that has accumulated over the century. These items tell history as people remember it, evoking the tastes, smells, sights and sounds of the past. There is much that will evoke happy memories - from the first Kit-Kat to Beatlemania, Meccano to The Picture Post. The 20th century has been the age of the brand name - from Bisto to Barbie, and these names have become a universal language that unites us. It is this language and the way of life that it evokes that this book celebrates so vividly. Remember When will be an absorbing sourcebook of images and anecdotes for all those interested in our past - from graphic designers to school children, social historians to lovers of nostalgia. - A new way of looking at history, traced through the objects that surrounded us all. - Will appeal to a wide range of readers - from graphic designers and historians to grandparents and schoolchildren.- Full-colour images taken from the acclaimed Robert Opie Collection of advertising and packaging.
Include index
Keywords: Great Britain